Critical insights into the recent advancements and future prospects of zinc ion battery electrolytes in aqueous systems - Kou L.; Wang Y.; Song J.; Ai T.; Li W.; Wattanapaphawong P.; Kajiyoshi K.; Ghotbi M.Y.; Feng Y. (Royal Society of Chemistry, 2025)
In recent years, aqueous zinc ion batteries (ZIBs) have emerged as promising candidates for energy storage systems due to their inherent safety, environmental friendliness, and cost-effectiveness. This review provides a comprehensive overview of the advancements and prospects of aqueous electrolytes for ZIBs. The introduction outlines the background and significance of ZIBs, emphasizing their advantages over organic electrolytes while elucidating challenges and limitations associated with aqueous electrolytes. The foundational knowledge section revisits the fundamental principles of ZIBs, including their basic working mechanism and the composition and properties of aqueous electrolytes. Subsequently, the review delves into the recent research developments, highlighting the design and synthesis of novel aqueous electrolytes and discussing key technological breakthroughs in advanced electrolyte formulations. Relevant research works are presented to provide concrete examples of ongoing progress in this field. This review concludes by summarizing the latest advancements in aqueous electrolytes for ZIBs and emphasizing the significance and potential of this research area. Furthermore, future trends, challenges faced, and potential solutions are discussed, shedding light on the evolving role of ZIBs in the energy sector. Overall, this review serves as a valuable resource for researchers, scientists, and engineers working on the development of advanced energy storage technologies. ? 2024 The Royal Society of Chemistry.